Konfession und Sozialstruktur: Vergleichende Analysen auf geographischer Grundlage - Hahn, Helmut (ERDKUNDE, 1958)
The object of this paper is to show, by progressing historically as well as in space, some principal peculiarities of the social structure of two religious denominations, the Roman Catholic and the Protestant faith. Beginning with a situation of simple social structure, an investigation was made of the development in agricultural areas of population surplus and emigration so as to faci itate a better understanding of the situation in the socially more highly differentiated regions of population concentration. The investigations of these two denominations in the area of the Hunsrück, where the custom of divided in heritance prevails, showed that the Catholics are characterized by a higher birth rate which, because of a relatively lesser emigration, results in an increase of the population density; this exerts a direct influence on property owning, i. e. size of holdings. In turn this brings about a different occupational structure of the two denominations. In order to prove that these differentiations are not merely results of the different family sizes of the denominations but in the last instance are due to a contrasting economic behaviour, a supplementary investigation was necessary. Despite the limited economic opportunities existing there this point emerged already in the Hunsrück but it became quite clear in the second area investigated, the district of Tecklenburg where the custom of undivided inheritance prevails. Since in an area of undivided inheritance the number of farm holdings remains relatively constant, the Catholics, because of their great population pressure, are forced to increased emigration, and they also show a social structure which differs from that of the Protestants. The economic behaviour in the Tecklenburg district peculiar to the denominations becomes apparent in the manner in which the custom of inheritance is applied, and it emerged also in the election results for the first federal parliament in 1949. Especially in this region the compulsory measures of past rulers spurred the Catholics to achievements which were in no way second to the economic success of the members of the Protestant free churches in the Bergische Land. In observing the situation in the mainly industrial and urban areas we find the rural emigrants of both denominations in the nonagricultural branches of commerce and other occupations in positions closely allied to their initial status. Most Catholics come to the towns not without any means, but largely without higher education or advanced training. Furthermore since owing to the higher birth rate they make up a higher proportion of the urban influx, a number of differentiations must result by necessity in the receiving areas. The existence of these differentiations can be shown quantitatively by suitable processing of the 1950 census data of selected urban and rural districts. The Catholic population provides a higher proportion of the working classes, largely of the unskilled rather than skilled labour. In the social group of the self-employed, Protestants have the greater share in particular in commerce, banking and insurance, with an emphasis on the larger enterprises. The situation is similar with salaried employees and civil servants where Protestants show a preponderance in the higher scales, especially in public utilities and transport (Federal Post, Federal Railways), whereas the Catholics are in the majority in the groups of the lowest scales. It becomes apparent that religious denomination has not only a bearing on social status but also on certain branches of the national economy. A social geographical analysis of the connexions between denomination and social structure shows beyond doubt that there is a different attitude of these denominations towards economic life. The denominations as social groups emerge in this way as landscape forming agents of the first order.